Satisfaction Level of the Blind on Urban Transportation System in Greater Jakarta - Putranto, Leksmono Suryo; Putri, Dwi Amintra (International Journal of Integrated Engineering, 2018)
The availability of transportation infrastructure and facilities accessible for people with disability is required to provide convenience for people with disability in conducting daily activities independently. Data collection was conducted on a Focus Group Discussion (FGD) with of 13 blind people as subjects of research. They are members of Indonesian Visually Impaired Union (PERTUNI). Other sources of data were field observation and secondary data of design and service standards. Transportation related to blind people on this reseacrh consisted of Urban Railway System and Transjakarta Bus Rapid Transit System. Observation, FGD, and the study of design and service standards of the railway station include type of information service, ticket counter, tap card equipment, priority seats, and toilets. Observation, FGD, and the study of design and service standards of Transjakarta line includes pedestrian facilities, stairs, guiding block, type of service information, officers, convenience of Transjakarta boarding/ alighting, and TJ card. In general blind people in Greater Jakarta have not been provided with easiness and accessible urban public transport mode since universal design principle have not been totally adopted, e.g. in terms of gap between train and station platform, auditory information in the bus, gender identification of toilets, conditon of guiding blocks etc